Working with a secular age: interdisciplinary perspectives on Charles Taylor's master narrative - Zemmin, Florian; Jager, Colin; Vanheeswijck, Guido; Taylor, Charles (Religion and its others, 2016)
Charles Taylor’s monumental book A Secular Age has been extensively discussed, criticized, and worked on. This volume, by contrast, explores ways of working with Taylor’s book, especially its potentials and limits for individual research projects. Due to its wide reception, it has initiated a truly interdisciplinary object of study; with essays drawn from various research fields, this volume fosters substantial conversation across disciplines.